Decisions on Extending Group Membership: Evidence from a Public Good Experiment - Christian Grund; Christine Harbring; Kirsten Thommes; Katja Rebecca Tilkes (Institute of Labor Economics (IZA), 2019)
We experimentally analyze whether the opportunity to receive a permanent contract motivates temporary group members in a public good setting and how this affects the other group members. We compare an exogenous and an endogenous decision mechanism to extend the temporary agent's group membership. The exogenous mechanism to extend the contract is modeled by a random draw. In the endogenous setting, one other group member decides about the temporary agent's future group membership. Our results reveal that both — the decision to extend a contract and the decision mechanism itself — affect not only the temporary group member's effort but also the efforts of the permanent group members and, ultimately, also cooperation within the group after the decision has been made.
Keywords: C9; M5; 330; cooperation; experiments; groups; public good games; teams; temporary employment